Being Edgy in Health Professions Education: Concluding the Philosophy of Science Series. (July 2020) - MacLeod, Anna; Ellaway, Rachel H.; Paradis, Elise; Park, Yoon Soo; Young, Meredith; Varpio, Lara
Abstract : The philosophy of science is concerned with what science is, its conceptual framing and underlying logic, and its ability to generate meaningful and useful knowledge. To that end, concepts such as ontology (what exists and in what way), epistemology (the knowledge we use or generate), and axiology (the value of things) are important if somewhat neglected topics in health professions education scholarship. In an attempt to address this gap, Academic Medicine has published a series of Invited Commentaries on topics in the philosophy of science germane to health professions educational science. This Invited Commentary concludes the Philosophy of Science series by providing a summary of the key concepts that were elucidated over the course of the series, highlighting the intent of the series and the principles of ontology, epistemology, axiology, and methodology. The authors conclude the series with a discussion of the benefits and challenges of cross-paradigmatic research.